2005
DOI: 10.1063/1.1991979
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic gating of an organic electrochemical transistor

Abstract: A microfluidic-based organic electrochemical transistor is reported. The integrated microfluidic channel not only confines and directs the flow of liquid electrolyte over the active layer of the transistor but also provides the gate electrode for the transistor. The active layer employed in this work is poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), which results in a transistor that is inherently “on” but that can be turned “off” through application of a positive gate voltage. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 17 publications
2
68
0
Order By: Relevance
“…[1][2] One example is organic electronic ion pumps, 15 which are able to precisely control the flow of ions between two reservoirs, and have been used to pump neurotransmitters and stimulate cochlear cells in the inner ear of a guinea pig. [3][4][5] Another example is organic electrochemical transistors (OECTs) that are being developed for a variety of biosensing 20 applications, including the detection of ions, [6][7][8] metabolites (such as glucose 9 and lactate 10 ) and antibodies. 11 Originally developed by Wrighton in the 80's, 12 OECTs consist of a conducting polymer film (channel of the transistor) in contact with an electrolyte.…”
mentioning
confidence: 99%
“…[1][2] One example is organic electronic ion pumps, 15 which are able to precisely control the flow of ions between two reservoirs, and have been used to pump neurotransmitters and stimulate cochlear cells in the inner ear of a guinea pig. [3][4][5] Another example is organic electrochemical transistors (OECTs) that are being developed for a variety of biosensing 20 applications, including the detection of ions, [6][7][8] metabolites (such as glucose 9 and lactate 10 ) and antibodies. 11 Originally developed by Wrighton in the 80's, 12 OECTs consist of a conducting polymer film (channel of the transistor) in contact with an electrolyte.…”
mentioning
confidence: 99%
“…[81] In addition to fluorescence-detection methods, EC-OTFTs and OFETs sensors have been incorporated into microfluidics. [82,83] Thus, organic electronics have been combined with microfluidics in order to sense and record species of an analyte. Conversely, organic electronics can be used also to regulate the flow of the analyte itself inside the channel, enabling the analytes to intermix with reagents in a desired chronological order.…”
Section: Organic Bioelectronics In Microfluidicsmentioning
confidence: 99%
“…Further, the sensor when operated as a transistor has shown to be more sensitive than a chemiresistor by an order of magnitude [3]. It has also been shown that the gate electrode in an electrochemical transistor can be integrated into the ceiling of a microfluidic channel to realize the "lab-on-chip" concept [5]. However, a major performance constraint of these electrochemical sensors is the response time which ranges from ∼60 seconds to 30 minutes [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The BC geometry has the drain-source electrodes staggered with respect to the electrolyte/conducting polymer interface, while the TC geometry has the coplanar structure of drain-source/conducting polymer interface and the electrolyte/conducting polymer interface. It may also be mentioned that the organic electrochemical transistor used commonly for biological sensing [2,5] employs TC geometry…”
Section: Introductionmentioning
confidence: 99%